Kegiatan Pendampingan Pelaporan SPT Tahunan oleh Relawan Pajak bagi Wajib Pajak Orang Pribadi di Wilayah Sidoarjo Barat - Vivianti Indar Yusnia; Achmad Wicaksono (Svarga Pena : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to improve the compliance of Individual Taxpayers (WPOP) in submitting their Annual Tax Returns (SPT) in the West Sidoarjo area. The method used involves assisting in the submission of Annual Tax Returns through education and technical guidance provided by tax volunteers from Nahdlatul Ulama University of Sidoarjo. This activity includes education on the procedures for filling out the SPT, simulation of the reporting process, and direct assistance for taxpayers facing difficulties. The results of this activity show a positive impact, marked by an increase in the number of WPOP who submit their SPT on time and in compliance with tax regulations. Furthermore, the error rate in filling out the SPT significantly decreased, leading to a better understanding of tax obligations among the community. The benefits felt by the participants include increased tax literacy, ease in the reporting process, and heightened awareness of the role of taxes in regional development. The success of this program is expected to serve as a sustainable practice to encourage tax compliance in other regions. The findings highlight the importance of collaboration between educational institutions, volunteers, and the community in improving tax compliance through an educational and practical approach.